Phép chuyển từ đặc tả ẩn tang thành chương trình logic - Anh, Duong Tuan (Journal of Computer Science and Cybernetics, 2018)
This paper presents a way to transform an initial specification of a problem into a PROLOG program by introducing recursion and through a data retinement step. This transformation contributes to a programming methodology which intends to derive programs from formal specifications.